Transcending barriers: the role of Purépecha women in cultural preservation and community building - Galindo Castro, Saira Genoveva (2023)
In the context of the Purépecha community, women play a fundamental role in the organization and structuring of daily life within the receiving space. These Purépecha women, known as uarhitiicha, reproduce in the new environment the same gender roles and forms that they would employ in their places of origin. However, the transition to a supermodern environment also brings challenges and cultural shocks. Despite assuming the same ethnic obligations related to their gender, they are also burdened with responsibilities that would normally fall exclusively on men. This socio-cultural shift responds to the specific needs of migrating Purepecha ethnic families, as maintaining gender differentiation would make it difcult for them to function as a family unit.